Migraine prevalence in inflammatory bowel disease patients: A tertiary‐care centre cross‐sectional study. (16th May 2017) - Moisset, X.; Bommelaer, G.; Boube, M.; Ouchchane, L.; Goutte, M.; Dapoigny, M.; Dallel, R.; Guttmann, A.; Clavelou, P.; Buisson, A.
Abstract: Background: Inflammatory bowel diseases (IBD) are systemic, chronic inflammatory conditions that predominately affect the gastrointestinal tract and can induce abdominal pain. Besides, many IBD patients complain about headaches in daily practice. The objective was to assess the prevalence of headaches, including migraines and pain with neuropathic characteristics (NC), in IBD patients compared to historical controls from the general population. Methods: Overall, 203 consecutive tertiary‐care centre patients completed validated self‐administered questionnaires and benefitted from a clinical evaluation performed by an IBD physician at the same time. Results: In our cohort, 75% of the patients experienced pain in the previous 3 months. Migraine prevalence was two‐fold higher in IBD patients compared to the general population (41% vs. 21.3%, p < 0.001). Migraine was associated with a younger age, female gender and higher depression scores. Although migraine impact was very important for 30% of the patients (61/203), specific acute therapeutics were prescribed in only 22% of cases (18/83). Chronic pain with NC was more frequent than in the general population (11.3% vs. 6.9%, p = 0.012) and was strongly associated with the presence of extra‐intestinal manifestations ( p < 0.001). Abdominal pain concerned 19% of the patients during the previous week and was, as expected, associated with disease activity. Conclusions: Migraine prevalence is strongly increased in IBD patients followed in tertiary care. A systematic screening for migraine should be done by IBD physicians in daily practice to provide adequate therapeutics. Further studies are needed to confirm whether migraine should be classified as IBD extra‐intestinal manifestations. Significance: Migraine prevalence was two‐fold higher in IBD patients compared to the general population, was generally poorly treated and a systematic screening for migraine should be done by IBD physicians in daily practice to provide adequate therapeutics.